2010
DOI: 10.1097/cpm.0b013e3181da8a0e
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoscopy in Uremic Patients

Abstract: Uremia is associated with an increased risk of bleeding by virtue of alteration in platelet adhesion. Pulmonologists are frequently called upon to perform flexible bronchoscopy in patients with chronic renal insufficiency. The high blood urea nitrogen levels may predispose these patients to a high risk of bleeding complications with bronchoscopic procedures. We carried out a literature review to evaluate the myth that bronchoscopy is unsafe in uremic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Some recommend desmopressin as an adjunct to mitigate this risk because it has been proven to decrease bleeding time in patients with uremia in small studies. 25,26 Limited data exist on the safe minimum threshold for platelet count when performing endobronchial or transbronchial lung biopsies. 27 Papin et al 28 reported a series of 24 patients with thrombocytopenia (mean platelet count, 30,000/mm 3 AE 16,500/mm 3 ) undergoing transbronchial lung biopsies wherein 20.8% had bleeding complications.…”
Section: Procedural Preparedness and Preventionmentioning
confidence: 99%
“…Some recommend desmopressin as an adjunct to mitigate this risk because it has been proven to decrease bleeding time in patients with uremia in small studies. 25,26 Limited data exist on the safe minimum threshold for platelet count when performing endobronchial or transbronchial lung biopsies. 27 Papin et al 28 reported a series of 24 patients with thrombocytopenia (mean platelet count, 30,000/mm 3 AE 16,500/mm 3 ) undergoing transbronchial lung biopsies wherein 20.8% had bleeding complications.…”
Section: Procedural Preparedness and Preventionmentioning
confidence: 99%
“…An increased risk of bleeding with TBLB [ 1 , 22 ] could not be documented in a recent retrospective study [ 33 ]. Patients on chronic haemodialysis received haemodialysis and desmopressin intravenously before the procedure, and some authors suggest this approach [ 34 ]. Most pulmonologists, however, do not consider a high creatinine value as a contraindication to perform TBLB, and only 37% of them consider it appropriate to administer desmopressin prior to TBLB in uraemic patients [ 26 ].…”
Section: Risk Factorsmentioning
confidence: 99%